2020
DOI: 10.1007/s00264-020-04504-1
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad and the rude peer-review

Abstract: Peer-review is the core of the editorial process and the basis of the publication system. The quality of peer-review depends on the quality of the peer-reviewers. Peer reviewers are supposed to ensure that journals publish high-quality science by evaluating manuscripts and offering suggestions for improvement. Peer-reviewers are typically selected based on their expertise in the areas of research associated with the submitted manuscripts. Although being a peer-reviewer is sometimes frustrating, communication b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 29 publications
0
58
0
1
Order By: Relevance
“…13 This process may be affected by some factors, especially those related to the reviewers, if they are young with less experience, lacking skills, and had no enough training on properly performing this process. 12 Gazendam et al found that the mean time from submission to publication was 13 ± 12 days (median 10 and range, 0e113 days), 14.9% of the articles were published within seven days of submission. 3 We reported nearly the same trend in orthopaedic publications related to Covid-19, where the mean time from submission to acceptance was 14.3 ± 15.8 days (median 9, the range was from 0 to 74), and 44% of the articles were accepted within the first week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 This process may be affected by some factors, especially those related to the reviewers, if they are young with less experience, lacking skills, and had no enough training on properly performing this process. 12 Gazendam et al found that the mean time from submission to publication was 13 ± 12 days (median 10 and range, 0e113 days), 14.9% of the articles were published within seven days of submission. 3 We reported nearly the same trend in orthopaedic publications related to Covid-19, where the mean time from submission to acceptance was 14.3 ± 15.8 days (median 9, the range was from 0 to 74), and 44% of the articles were accepted within the first week.…”
Section: Discussionmentioning
confidence: 99%
“…The essence of the rigorous peer-review process is to catch the misconduct and shortcomings of scientific articles before and not after it being published; it is considered as the foundation for the integrity of scientific findings in the medical field. 11 , 12 Although this process had been practiced by most of the medical journals over decades, however, the debate regarding the integrity and quality of this process still exists. 13 This process may be affected by some factors, especially those related to the reviewers, if they are young with less experience, lacking skills, and had no enough training on properly performing this process.…”
Section: Discussionmentioning
confidence: 99%
“…We try to identify and warn the authors for this type of behaviour. Finding good reviewers in crisis is not easy, but it turned out to be less difficult compared to other occasions such as summer holidays; we were pleased to see that the journal's reviewers reply promptly and accept a review assignment, and return on time with a good and constructive review [10,11]. The editors and reviewers of the journal opt for quality publications to increase the impact of the journal and the visibility of the submitted/ published papers [12].…”
Section: Orthopaedic Sciencementioning
confidence: 99%
“…Any submitted work is subjected to a demanding, constructive and objective process of peer-review which is still the best method to validate the quality of the accepted papers, although also flawed with biases [44]. In this regard, some journals have notorious high rejection rates [38,45].…”
Section: Useful and Useless Publicationsmentioning
confidence: 99%